EPISTEMOLOGI TAFSĪR QUR`ᾹN KARĪM KARYA MAHMUD YUNUS - Matsna Afwi Nadia (Tanzil: Jurnal Studi Al-Quran, 2023)
This article explains the thoughts of Mahmud Yunus in studying the epistemology of Tafsīr Qur`ān Karīm which is in Indonesian, complete in 30 chapters, to test its truth or to what extent the interpretation can be justified. According to the author, what is interesting to discuss: first, what are the sources used as references Mahmud Yunus in Tafsīr Qur`ān Karīm, secondly, what is the method of Mahmud Yunus in writing his book and thirdly, what is the validity of Mahmud Yunus's interpretation in Tafsīr Qur`ān Karīm. In order to achieve this purpose, this study uses analysis-based library research methods. The results of this study show: that the sources of interpretation referred to by Mahmud Yunus in Tafsīr Qur`ān Karīm include an-naql and al-aql sources, namely the Qur’an, hadith, qaul companions, qaul tabiin, holy books and opinions of scholars, reasoning, Arabic, scientific discoveries or scientific theories, and reality. However, the use of the al-'aql source is more dominant in its interpretation so that it is classified into the interpretation of bi al-ra'yi. Regarding the validity of his interpretation, Mahmud Yunus adheres to the correspondence theory of truth in which his interpretation of the kauniyah verses can be said to be in accordance with reality and scientific facts. Besides that, he also adheres to a pragmatic theory in which he tries so that the product of his interpretation can be an alternative solution for solving socio-religious problems faced by society.